OsKAT1 is a short Shaker potassium channel involved in root-to-shoot potassium translocation and contributes to rice grain yield - Shunying Yang; Thanh-Hao Nguyen; Cécile Fizames; Junlin Li; Sheliang Wang; Aurore Vernet; Emmanuel Guiderdoni; Shaofei Wang; Yixiu Guo; Weiwei Zhang; Tianqi Wei; Yanan Huang; et al. (Proceedings of the National Academy of Sciences, 2026)
Shaker potassium channels play essential roles in K + uptake and distribution in plants. Studies on Shaker channels in Arabidopsis have provided a paradigmatic framework, but the rice genome encodes an additional member, OsKAT1, whose function remians poorly defined. OsKAT1-type channels are characterized by an innately short cytosolic C terminus, forming a unique clade of monocot-specific short Shakers that is prevalent in Poaceae species. In rice, OsKAT1 is predominantly expressed in the root stele. Disruption of OsKAT1 (KO mutation) leads to a significant reduction in K + secretion into the xylem sap delivered to the shoot. Patch-clamp experiments on root stele protoplasts of WT and KO plants indicate that OsKAT1 functions as an inward channel. Functional analyses in Xenopus oocytes reveal that despite activating at weakly negative voltages, OsKAT1 is intrinsically incapable of mediating substantial outward currents—a property attributed to its truncated C terminus. Together with outward K + channel activity, this feature enables stelar cells to remain significantly permeable to K + around the K + equilibrium potential. When expressed in Arabidopsis , OsKAT1 contributes to K + transport in the xylem sap, but only in wild-type plants that express SKOR, a Shaker channel specialized for this role. These results demonstrate that OsKAT1 constitutes a component of K + translocation to shoots and shed light on the energization and regulation underlying this function. Moreover, OsKAT1 is shown to improve rice adaptation to environmental conditions and enhance grain yield under field conditions through its facilitating root-to-shoot ion translocation.